Adolescent Coping in an Academic Context: Adaptation of a Multidimensional Measure - Miguel Morales-Castillo (Universidad Autónoma de Baja California, 2022)
This study examines forms of coping with sources of academic tension, as assessed by an adaptation of the Multidimensional Measure of Coping (MMA, in Spanish), an instrument that identifies how adolescents respond to the challenges of education. The adaptation of the MMA involved a sample of 1,602 Colombian adolescents (mean age = 12.8; standard deviation = .98), including both male (49.2%) and female students from public (73.2%) and private schools. Confirmatory factor analysis was used to establish the validity of the instrument. The correlations calculated were used to evaluate the convergent and discriminant validity of the MMA scales, with "school adjustment" used as a contrast variable. Measurement invariance was addressed in a multi-group comparison. The indicators yielded by this research are adequate to consider the reported adaptation of the MMA valid and reliable for the sample studied.